Mortality rates at 10 years after metal-on-metal hip resurfacing compared with total hip replacement in England: retrospective cohort analysis of hospital episode statistics. - Kendal, A; Prieto-Alhambra, D; Arden, N; Carr, A; Judge, A (2013)
OBJECTIVES: To compare 10 year mortality rates among patients undergoing metal-on-metal hip resurfacing and total hip replacement in England. DESIGN: Retrospective cohort study. SETTING: English hospital episode statistics database linked to mortality records from the Office for National Statistics. POPULATION: All adults who underwent primary elective hip replacement for osteoarthritis from April 1999 to March 2012. The exposure of interest was prosthesis type: cemented total hip replacement, uncemented total hip replacement, and metal-on-metal hip resurfacing. Confounding variables included age, sex, Charlson comorbidity index, rurality, area deprivation, surgical volume, and year of operation. MAIN OUTCOME MEASURES: All cause mortality. Propensity score matching was used to minimise confounding by indication. Kaplan-Meier plots estimated the probability of survival up to 10 years after surgery. Multilevel Cox regression modelling, stratified on matched sets, described the association between prosthesis type and time to death, accounting for variation across hospital trusts. RESULTS: 7437 patients undergoing metal-on-metal hip resurfacing were matched to 22,311 undergoing cemented total hip replacement; 8101 patients undergoing metal-on-metal hip resurfacing were matched to 24,303 undergoing uncemented total hip replacement. 10 year rates of cumulative mortality were 271 (3.6%) for metal-on-metal hip resurfacing versus 1363 (6.1%) for cemented total hip replacement, and 239 (3.0%) for metal-on-metal hip resurfacing versus 999 (4.1%) for uncemented total hip replacement. Patients undergoing metal-on-metal hip resurfacing had an increased survival probability (hazard ratio 0.51 (95% confidence interval 0.45 to 0.59) for cemented hip replacement; 0.55 (0.47 to 0.65) for uncemented hip replacement). There was no evidence for an interaction with age or sex. CONCLUSIONS: Patients with hip osteoarthritis undergoing metal-on-metal hip resurfacing have reduced mortality in the long term compared with those undergoing cemented or uncemented total hip replacement. This difference persisted after extensive adjustment for confounding factors available in our data. The study results can be applied to matched populations, which exclude patients who are very old and have had complex total hip replacements. Although residual confounding is possible, the observed effect size is large. These findings require validation in external cohorts and randomised clinical trials.